A new approach to automation of black tea fermentation process with electronic nose - Bilge Han Tozlu (Automatika, 2018)
Manufacturing of black tea is a complex process consisting of plucking, withering, curling, fermenting, drying, determining of quality, and packaging stages. Nowadays, tea quality is determined by two methods. Either chemical analysis method is used or tea tasters give quality scores by tasting, smelling, and visual inspection. By means of recent studies, tea quality can also be determined by electronic nose technology. The quality of tea is generally related with the fermentation stage. In this work, an electronic nose, which determines the quality of tea during the fermentation process in real time from only its odour, was made, and the fermentation band was controlled by this electronic nose. Fermentation bands of a tea factory in the Çayeli District of Rize, Turkey have been simulated and controlled via LabVIEW simulation software by using real odour values measured in the factory with the electronic nose. In the study, a new fermentation band system has been designed to function with the electronic nose. This section of the study has been performed in the simulation environment due to the high cost of physical system setup. With the method proposed in this study, tea factories will be able to increase their production capacity with higher quality.